Stem/progenitor cells in the cerebral cortex of the human preterm: a resource for an endogenous regenerative neuronal medicine? - Laura Vinci; Alberto Ravarino; Clara Gerosa; Maria Cristina Pintus; Maria Antonietta Marcialis; Viviana Marinelli; Gavino Faa; Vassilios Fanos; Rossano Ambu (Hygeia Press di Corridori Marinella, 2016)
The development of the central nervous system represents a very delicate period of embryogenesis. Premature interruption of neurogenesis in human preterm newborns can lead to motor deficits, including cerebral palsy, and significant cognitive, behavioral or sensory deficits in childhood. Preterm infants also have a higher risk of developing neurodegenerative diseases later in life. In the last decade, great importance has been given to stem/progenitor cells and their possible role in the development and treatment of several neurological disorders. Several studies, mainly carried out on experimental models, evidenced that immunohistochemistry may allow the identification of different neural and glial precursors inside the developing cerebral cortex. However, only a few studies have been performed on markers of human stem cells in the embryonic period. This review aims at illustrating the importance of stem/progenitor cells in cerebral cortex during pre- and post-natal life. Defining the immunohistochemical markers of stem/progenitor cells in the human cerebral cortex during development may be important to develop an "endogenous" target therapy in the perinatal period.   Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano